If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -5 = 4x + 5 Reorder the terms: -5 + -6x = 4x + 5 Reorder the terms: -5 + -6x = 5 + 4x Solving -5 + -6x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + -6x + -4x = 5 + 4x + -4x Combine like terms: -6x + -4x = -10x -5 + -10x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -10x = 5 + 0 -5 + -10x = 5 Add '5' to each side of the equation. -5 + 5 + -10x = 5 + 5 Combine like terms: -5 + 5 = 0 0 + -10x = 5 + 5 -10x = 5 + 5 Combine like terms: 5 + 5 = 10 -10x = 10 Divide each side by '-10'. x = -1 Simplifying x = -1
| -3=3+v | | 13=6+(-r) | | 5+3*b=8-5*b | | 2x^2+19x+30=0 | | 2x*2+4x+4800=0 | | 6x+7-4x+5= | | 19n=-456 | | 486=27x | | 9(7y-3)-(7y+2)= | | -r-1=-10 | | -6-3k=-2k-(k+6) | | -101+4x=-7x+119 | | 7(6x+2)=392 | | 2-5b=24 | | 4(6-12)+2(7-11)= | | -5-n=-15 | | 10x+5+11x-5= | | 17=-3w+2 | | X^2+4x-5=2x(x-1) | | -4(x+2)=-24 | | Z=4-2i | | 2x-7=7x-22 | | 3x+69=45 | | 1212= | | 38.83+.50x=c | | 5x-91=-3x+109 | | 7x-8x-6= | | p+10=7 | | 6k-3k=0 | | 6(R-7)=-162 | | -x-4=4x+6 | | -3-11=6y+16 |